2007
DOI: 10.3748/wjg.v13.i6.964
|View full text |Cite
|
Sign up to set email alerts
|

Fatal liver failure caused by reactivation of lamivudine-resistant hepatitis B virus: A case report

Abstract: We present a case of fetal liver failure caused by the activation of lamivudine-resistant hepatitis B virus (HBV) nine months after lamivudine treatment. A 57-year old man visited our hospital for the treatment of decompensated chronic hepatitis B. Lamivudine was started in December 2001. Subsequently, serum HBV was negative for HBV DNA with seroconversion from HBeAg to anti-HBe and improvement of liver function. However, HBV DNA and HBeAg were again detected in September 2002. He was complicated by breakthrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In patients infected with HBV genotype C, several polymerase mutations, including rtL80V/I, rtL180M and rtM204I, were associated with significantly higher viral loads, increased LAM resistance and disease exacerbation (9). In addition, the coexistence of rtM204V/I with rtL80V/I occurred at the time of viral breakthrough in a patient with fatal liver failure caused by the activation of LAM‐resistant HBV 9 months after LAM treatment (27). To clarify the adverse effects of the rtL80V/I mutation on clinical outcomes, further studies are needed in patients harbouring rtL80V/I.…”
Section: Discussionmentioning
confidence: 99%
“…In patients infected with HBV genotype C, several polymerase mutations, including rtL80V/I, rtL180M and rtM204I, were associated with significantly higher viral loads, increased LAM resistance and disease exacerbation (9). In addition, the coexistence of rtM204V/I with rtL80V/I occurred at the time of viral breakthrough in a patient with fatal liver failure caused by the activation of LAM‐resistant HBV 9 months after LAM treatment (27). To clarify the adverse effects of the rtL80V/I mutation on clinical outcomes, further studies are needed in patients harbouring rtL80V/I.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in vivo , as drug-resistant mutants emerge, there is an increase in viral load and serum alanine aminotransferase levels as well as a deterioration of liver histology. Indeed, lamivudine-resistant mutants have also been associated with death in several case studies (Kagawa et al, 2004; Kim et al, 2001; Suzuki et al, 2007; Wang et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…In YMDD variants, the methionine of the YMDD motif in HBV polymerase is substituted with either isoleucine, designated as YIDD, or valine, designated as YVDD. Much clinical data has indicated that patients who have developed HBV YMDD mutations show deterioration of their physical condition, and rebound of virus load in their serum [12][13][14] . In this study, we constructed the eukaryotic expression plasmids of HBV genotype C full-length genome, which contained wild-type, YVDD mutation or YIDD mutation, respectively.…”
Section: Introductionmentioning
confidence: 99%